Health system preparedness among African countries for disease outbreaks using the World Health Organisation Health systems framework: an awakening from the recent mpox outbreak - Ayesiga, Innocent; Magala, Primrose; Ovye, Aghu; Gmanyami, Jonathan Mawutor; Atwau, Pius; Ismaila, Esther; Muwonge, Henry; Ediamu, Tom Didimus; Atimango, Lorna; Dogo, Joy Malle; Okoro, Lenz Nwachinemere; Mulogo, Edgar M.; et al. (Frontiers in Tropical Diseases, 2025)
Over time, numerous health issues have challenged Africa’s health systems, including reemerging and emerging pandemics and epidemics. International health bodies, such as the World Health Organisation (WHO), have developed various frameworks to help health systems maintain service delivery to their respective communities and individuals. The WHO’s health system framework is a six-pronged strategy to enhance healthcare service delivery. However, emerging epidemics, such as mpox, have hindered the integration of these components. This review explored the health preparedness of African countries to mitigate emerging and re-emerging epidemics using the WHO health system framework with a focus on mpox. The review found most African countries lack adequate health products, such as vaccines against mpox, and have limited human resources available to care for affected individuals. For instance, Africa’s health worker staffing is estimated at 1.55 per 1000 people compared to the 4.45 per 1000 WHO threshold. Many African countries, like Somalia, Uganda, Eritriea lack efficient health preparedness plans to enhance their readiness to address the epidemic. Nevertheless, these plans provide detailed information regarding mpox risks and how to mitigate them based on risk factors, such as reducing zoonotic spillover. Healthcare financing in is still challenged in many African countries like Uganda, Tanzania, and Ghana due to limited budgetary allocations, which affects the purchase and distribution of necessary resources for mpox prevention, control, and management. Cuts in funding from major donors, including United States Agency for International Development (USAID) and UK Aid (formerly known as Department of International Development, DFID), worsen the situation. However, African countries can leverage on innovation and risk factor mitigation, to fully equip their healthcare systems based on available frameworks for other re-emerging epidemics. Additionally, they must strategise avenues of self-sustenance, such as political commitment and depending on other resources to fund their health programs.